Annual report 2020: CGIAR Research Program on Water, Land and Ecosystems - CGIAR Research Program on Water, Land and Ecosystems (CGIAR Research Program on Water, Land and Ecosystems, 2021)
This Annual Report documents a firm foundation for results in all five Strategy impact areas of the One CGIAR Research and Innovation Strategy, demonstrating the relevance of WLE within the “systems transformation approach for food, land and water systems” that it maps out.